Investing Mineral Wealth in Development Assets : Ghana, Liberia and Sierra Leone - Boakye, Daniel (2012)
Promoting sustainable development calls for investing rents from exhaustible mineral resources into human, physical and social capital, so as to protect the wealth of countries and the economic opportunities of their citizens. This has been difficult in well-governed Ghana in the last decade; and might prove to be extremely challenging in post-conflict countries such as Liberia and Sierra Leone, where preference for the present is high and institutions to collect rents and convert them into effective investments weak. The paper reviews the countries' degrees of preparedness to confront the various challenges associated with ongoing mineral booms, and tries to identify country-specific policy areas of particular relevance and potential impact for sustainable development.